Study the variation in blood cell counts in patients with moderate to severe COVID-19 infection - Zaid Duraid Idrees Al-Hamdani; Rojan G. AL-Allaff; Bashar Sadeq Noomi (Zien Journals, 2023)
The current study aimed to evaluate some immune variables in COVID-19 patients for chronic and acute conditions, as the study included the collection of (120) blood samples for individualssuspected of having respiratory distress syndrome and of both sexes and a age ranging from 29 years to 60 years for a period from 15/12/2021 to 20/7/2022 from a hospital Nineveh AlAhly and Ibn Sina Governmental Hospital. The samples recorded in the study after the confirmation of the diagnosis of COVID-19 were divided into two groups, the first groupincluded (25) patients withchronic respiratory distress syndrome who are in the intensive care unit and need Ventilator support, the second group included (25) patients who suffer from moderate symptoms and the control sample included (25) blood samples for healthy individuals. Through the study, some immune variables of the study sample were evaluated, which included the total numbers of white blood cells, the absolute numbers of neutrophil, lymphatic, mononucleus, acidophilic cells.
Keywords: white; healthy; collection; samples